Adaptive response to pneumonectomy in puppies. Issue 6 (June 1981) - Thurlbeck, W M; Galaugher, W; Mathers, J
Abstract : When left pneumonectomy was performed on 9-week-old puppies, the right lung increased in weight, volume, surface area, and number of alveoli so that at age 20 weeks these variables were the same as those of both lungs of control animals and significantly larger than those of the right lung of control animals. The adaptive response of the right lung after pneumonectomy was greater in the lower lobe than in the middle or cardiac lobes. The number of alveoli per ml and the average interalveolar wall distance, hence the surface to volume ratio, was the same in both lungs of control animals and the same in the cardiac, middle, and lower lobes of their right lungs.